SYNTHESIS OF 3,4-DIMETHOXY ISOAMYL CINNAMIC AS THE SUNSCREEN COMPOUND FROM CLOVE OIL AND FUSEL OIL - Tutik Dwi Wahyuningsih; Tri Joko Raharjo; Iqmal Tahir (Indonesian Journal of Chemistry, 2002)
Synthesis of sunscreen compound 3,4-dimethoxy isoamyl cinnamic from clove oil and fusel oil has been done. The majoring component of clove oil that is eugenol has been isolated, followed with several chemical processes i.e. isomerization into isoeugenol, oxidation of the product to change into vanillin, then modification vanillin into veratraldehyde. From the fusel oil, we isolate isoamyl alcohol and modified by acetylation into isoamyl acetic. The final product could be produce by Claissen's condensation of isoamyl acetic and veratraldehyde to give 3,4-dimethoxy isoamyl cinnamic. All of the processes are followed with structure characterization using GC, IR, GC-MS and 1H-NMR spectroscopy. The result shown that compound has 46.98% purity and potent as the UV-B sunscreen's type (lmax = 313 nm). In-vitro sunscreen's activity of the compound was tested by UV-Vis spectrophotometry and resulting a maximum Sun Protection Factor value (SPFin-vitro) at low concentration, 10.25 mg/mL.